Fejér and Hermite-Hadamard Type Inequalities for Harmonically Convex Functions - Feixiang Chen; Shanhe Wu (Journal of Applied Mathematics)
We establish a Fejér type inequality for harmonically convex functions. Our results are the generalizations of some known results. Moreover, some properties of the mappings in connection with Hermite-Hadamard and Fejér type inequalities for harmonically convex functions are also considered.